The Influence of Green Marketing, Product Quality and Brand Image on Buying Interest in Bottled Drinking Water Brand Le Minerale - Randi Randi; Mimi Kurnia Nengsih (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The purpose of this study was to determine the effect of green marketing, product quality and brand image on consumer buying interest. This type of research is quantitative with a descriptive approach. The research population was all students of the Faculty of Health Sciences, Universitas Muhammadiyah Bengkulu. The number of research samples was 70 people. Data collection using a questionnaire. Data analysis techniques using multiple linear regression analysis. The results showed that partially green marketing has a positive and significant effect on purchase intention, product quality has a positive and significant effect on purchase intention and brand image has a positive and significant effect on purchase intention. Simultaneously there is an influence of green marketing, product quality and brand image on buying interest decisions.